Giúp mình với
x^3-x=x^2+x
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^7+x^6+x^4+x^3+x^2+1\)
\(=x^4\left(x^3+x^2+1\right)+\left(x^3+x^2+1\right)\)
\(=\left(x^3+x^2+1\right)\left(x^4+1\right)\)
\(A=\dfrac{3x}{x-2}\cdot\sqrt{x^2-4x+4}\)
\(=\dfrac{3x}{x-2}\cdot\left(x-2\right)\)
=3x
\(B=\dfrac{-5y}{x+3}\cdot\sqrt{x^2+6x+9}\)
\(=\dfrac{-5y}{x+3}\cdot\left|x+3\right|\)
\(=\pm5y\)
\(a,4x^2\left(5x-3y\right)-5x^2\left(4x+y\right)\)
\(=20x^3-12x^2y-20x^3-5x^2y\)
\(=-17x^2y=-17\left(-2\right)^2.\left(-3\right)=204\)
\(b,\left(x-4\right)\left(x-2\right)-\left(x-1\right)\left(x-3\right)\)
\(=x^2-6x+8-x^2+4x-3\)
\(=-2x+5=-2.74+5=143\)
a) A \(=\)\(\frac{\left(2x^2+2x\right)\left(x-2\right)^2}{\left(x^3-4x\right)\left(x+1\right)}\)\(=\)\(\frac{2x\left(x+1\right)\left(x-2\right)^2}{x\left(x-2\right)\left(x+2\right)\left(x+1\right)}\)
\(=\)\(\frac{2\left(x-2\right)}{x+2}\)\(=\)\(\frac{2x-4}{x+2}\)
Tại x = \(\frac{1}{2}\)thì:
A = \(\frac{2.\frac{1}{2}-4}{\frac{1}{2}+2}\)\(=\)\(\frac{-3}{\frac{5}{2}}\)\(=\)\(\frac{-6}{5}\)
Bài 1:
a, \(\dfrac{3-\sqrt{x}}{x-9}=\dfrac{3-\sqrt{x}}{\left(\sqrt{x}-3\right)\left(\sqrt{x}+3\right)}=\dfrac{-1}{\sqrt{x}+3}\)
b, \(6-2x-\sqrt{9-6x+x^2}\)
\(=6-2x-\sqrt{\left(3-x\right)^2}\)
\(=6-2x-3+x\left(x< 3\right)\)
\(=3-x\)
Bài 2:
\(\sqrt{1-12x+36x^2}=5\)
\(\Leftrightarrow\sqrt{\left(1-6x\right)^2}=5\)
\(\Leftrightarrow\left|6x-1\right|=5\)
+) Xét \(x\ge\dfrac{1}{6}\) có:
\(6x-1=5\Leftrightarrow x=1\)
+) Xét \(x< \dfrac{1}{6}\) có:
\(1-6x=5\)
\(\Leftrightarrow x=\dfrac{-2}{3}\)
Vậy \(\left[{}\begin{matrix}x=1\\x=\dfrac{-2}{3}\end{matrix}\right.\)
x^3-x=x^2+x
x^3-x^2-x-x=0
x^3-x^2-2x=0
x^3-2x^2+x^2-2x=0
x^2(x-2)+x(x-2)=0
(x-2)(x^2+x)=0
x(x-2)(x+1)=0
Th1 : x=0
Th2 : x-2=0=>x=2
Th3 : x+1=0=>x=-1